Zakat Management Strategy at the At-Thohiri Semar Sharia Cooperative (Kst Semar) to Increase Public Trust - Abdullah (Penerbit Hellow Pustaka, 2024)
This research aims to explore zakat management strategies at the At-Thohiri Semar Sharia Cooperative (KST Semar) to increase public trust. This research uses qualitative methods with an empirical research type. Empirical research is a legal research method that attempts to see the law in a real sense or can be said to see, examine how the law works in society. The results of this research show, among other things: in terms of advantages and disadvantages. KST Semar's strategy to win the hearts of prospective muzakki who can become muzakki includes: using testimonials on social media; building publications such as billboards, brochures, and pamphlets; donation reports should be given to private muzzaki; and social media use maintenance. Factors that need to be taken into consideration in planning a zakat management strategy at KST Semar include: internal policies; framework and assets; member education and awareness. Fourth, partnerships with other zakat institutions; and welfare programs. The steps and components involved in moving or placing a zakat distribution program at KST Semar include: planning a zakat distribution program including targets and determining targets; Zakat fund collection includes mechanisms for collecting and separating funds